Energy auditing and electricity saving opportunities in BPOM laboratory of manokwari - Rehiara, Adelhard; Musa, Asril Yanto; Stepanus, Jamius Bin (Institute for Advanced Science Social, and Sustainable Future, 2023)
Energy auditing is a method of increasing energy efficiency. An energy audit is conducted to provide an overview of energy use, analyze the electrical system, and determine potential cost savings. The laboratory of the national food and drug agency (BPOM) in Manokwari has problems with electricity that often cause interruptions, power outages, and expensive bills. Therefore, this research was conducted to audit the energy used in the laboratory of the BPOM of Manokwari, with a building area of 1,484 m2 and an installed power of 105 kVA. In this laboratory building, a diesel generator with capacity of 5 kVA is installed as a backup energy source and the generator has its own installation line. According to the calculation results before auditing, the energy consumption intensity (IKE) value obtained per month is 10.18 kWh. Energy audit through lighting loads and air conditioning systems. Then the recommendation through energy savings for lights and air conditioners is 274.12 kWh/month and 639.32 kWh/month, respectively. Therefore, total savings are 913.44 kWh/month, or about IDR 1,541,886.72/month.